170k views
3 votes
Combine these two equations to find V(2) and V(1)-36= v(1) +2v(2)36=v(2)-V(1)

User Fredlahde
by
5.6k points

1 Answer

4 votes
Answer:

v(1) = -36, v(2) = 0

Step-by-step explanation:

The given system of equations is:

-36 = v(1) +2v(2).........................(1)

36 = v(2) - v(1)...........................(2)

Add equation (1) and (2) together

-36 + 36 = 3v(2)

0 = 3v(2)

v(2) = 0/3

v(2) = 0

Substitute v(2) = 0 into equation (1)

-36 = v(1) + 2(0)

-36 = v(1) + 0

v(1) = -36

Therefore, the solutions to the system of equations are:

v(1) = -36, v(2) = 0

User Scott Dillman
by
5.5k points